2017
DOI: 10.15562/phpma.v5i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Continuation rates for injectable contraception and intra-uterine device (IUD) at Banyuning Village, Buleleng District

Abstract: Background and purpose: Surveys on the proportion of contraception uptake have been regularly conducted in Indonesia, including Bali Province. However, very limited studies have explored contraceptive continuation rates. This study aims to examine continuation rates for injectable contraception and IUD including its determinants.Methods: A cross-sectional survey was conducted in Buleleng District. A total of 100 reproductive age women who ever used or currently using injectable contraception or IUD were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The discontinuation rate for participants receiving family planning services with other services (antenatal and postnatal clinics) was higher compared to users receiving their service in a separate room. A study in Banyuning Village (Indonesia) also showed that the quality of service can affect the continuous use of contraception [ 22 ]. Hence, quality of service may have a great impact in the continuation rate of contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…The discontinuation rate for participants receiving family planning services with other services (antenatal and postnatal clinics) was higher compared to users receiving their service in a separate room. A study in Banyuning Village (Indonesia) also showed that the quality of service can affect the continuous use of contraception [ 22 ]. Hence, quality of service may have a great impact in the continuation rate of contraceptive use.…”
Section: Discussionmentioning
confidence: 99%